Strategi Peningkatan Penjualan Menggunakan Sosial Media Instagram Pada UMKM Tas Kerajinan - Wahyu Susi Prastiyani; Budi Hartono (Jurnal Ilmiah Ekonomi Terpadu (Jimetera), 2022)
During this COVID-19 pandemic, many UMKM are maximizing the potential of small communities in their area. As an effort to encourage the marketing of their products online, digital marketing through online media is the right choice for UMKM to increase their product sales. This study aims to understand how digital marketing strategies are for small and medium-sized businesses that are not yet online and their impact on the competitiveness of these small and medium-sized businesses. This research uses literature study, raw data based on structured interviews and in-depth interviews with craftsmen. The results of this study indicate that most UMKM have used social media as a sales strategy. The most widely used social media is Instagram then followed by Facebook, E-marketing, new with traditional marketing. One of the perceived benefits of using social media is to increase the volume of product sales.